Post-Migration Outcomes and the Decision to Return: Processes and Consequences - Setrana, Mary Boatemaa (African Human Mobility Review, 2021)
This paper examines the decision-making processes of return migrants, especially since the 2001 introduction of government programmes to encourage the return of skilled migrants who have the capacity to contribute their quota to the development agenda of Ghana. Structured questionnaires were used to gather information on the migration trajectories of 120 return migrants. This was followed by interviews that primarily sought in-depth understanding of the decision-making processes of the return migrants. The findings indicate that these migrants were motivated by, among other factors, the availability of investment opportunities in Ghana, completion of education abroad, loss of jobs abroad, the decision to join family, feeling homesick and difficulty in integrating abroad. The paper recommends that home country governments should develop conducive policies appropriate for addressing the needs of the categories of returnees based on their decisions for coming home and how their skills and resources could be channelled into development.